All smiles - The Star (2012)
ALL SMILES: Deputy Prime Minister and Education Minister Tan Sri Muhyiddin Yassin is happy to pose with the children at the launching of the National Counselling and Education Carnival at Universiti Putra Malaysia (UPM), Serdang on Wednesday. Looking on are Malaysian Counselling Association (perkama) president Tan Sri Dr Nordin Kardi (left) and UPM vice-chancellor Datuk Dr Radin Umar Radin sohadi.